On the relation of theory and practice in foreign-language instruction - Szczodrowski, Marian (Glottodidactica, 2018)
Theoretical glottodidactic discussions are not only limited to the analysis and elucidation of the processes of teaching and learning foreign languages. They also create specific concepts for practical implementation. The essence of these processes is interpreted in many scholarly disciplines – for example, in didactics, glottocodematics, psycholinguistics – in the specific manner of that discipline. Thus, different theories recommended for glottodidactic practice propose their own/differing didactic-methodological solutions. The point of departure that is the language to be taught is, however, constituted by linguistic theories, which set out the distinctive features of that language, and particular glottodidactic theories are concerned with the effective acquisition and mastery of these features.